Structure of the Radical Form of Clostridial Flavodoxin: A New Molecular Model - Andersen, R. D. (1972)
Interpretation of a new electron-density map at 3.25-Å resolution has led to a somewhat revised model for the free radical (semiquinone) structure of flavodoxin from Clostridium MP. Although the general conformation of the molecule is very similar to that of oxidized Desulfovibrio vulgaris flavodoxin, flavin mononucleotide-protein interactions are not identical in the two flavodoxins. In the Cl. MP semiquinone molecule, the isoalloxazine ring appears to retain the essentially planar conformation characteristic of oxidized flavins; within the limits imposed by the resolution of the data, the map shows no evidence for bending of the isoalloxazine ring about N5-N10.